Frans Hals or not Frans Hals: Connoisseurship, Technical Analysis and Digital Tools - Tummers, Anna; G. Erdmann, Robert (Cultural Heritage Science, 2024)
Frans Hals is hailed as one of the three greatest painters of the Dutch seventeenth century along with Rembrandt and Vermeer. Of all seventeenth-century Dutch painters, Frans Hals is also the most controversial in as far as the exact scope of his oeuvre is concerned. Hals’s popularity, the lack of technical reference material as well as the differing views among experts as to the exact scope of his oeuvre make works in his style prone to doubts and misattributions. It has led to fierce debates and legal battles about the attribution of paintings done in his style. In this Open Access book, experts from Ghent University, Leiden University, Amsterdam University, Delft University of Technology, the Frans Hals Museum (Haarlem), the Rijksmuseum (Amsterdam), the Gemäldegalerie (Berlin) and the Metropolitan Museum of Art (New York) give surprising new insights into some of Hals’s most well-known paintings as well as into some of the most fiercely contested pictures in his style. Their insights result from in-depth study of a wealth of reference material: seventeenth-century sources, advanced technical analyses and newly developed digital visualisation tools. “Tummers and Erdmann have produced a work of ground-breaking new scholarship. They combine in-depth art historical study with new technical analyses and data visualisation tools in order to solve current issues in the attribution of paintings by Frans Hals. This book significantly sharpens our understanding of Hals’s virtuoso work process, his characteristic workshop practice, and his notion of authenticity. The rich data gathered for the case studies will be useful for a next generation of art historians and connoisseurs: digital tools enhance the human eye in matters of attribution.” Prof. Thijs Weststeijn, Professor of Art History before 1800, Utrecht University "Tummers bravely interrogates the history of connoisseurship and the seemingly never-ending search for attributions of paintings associated with Frans Hals. A series of well-chosen case studies of paintings rigorously subjected to the most current means of examination and scientific imaging by leading experts in the field extends our understanding of Hals, his manner of painting, and the possibilities for aligning traditional connoisseurship with technical studies and techniques. In the process, this book thoughtfully probes the merits, challenges, and potential of 21st-century digital tools alongside the role of visual analysis." Christopher D.M. Atkins, Van Otterloo-Weatherbie Director of the Center for Netherlandish Art at the Museum of Fine Arts, Boston